(untitled) (Global Conference on Medical and Health Sciences, 2026)
The rapid expansion of digital technologies has led to an unprecedented growth of healthcare data, creating new opportunities for improving medical services through big data analytics. This paper examines the role of big data in healthcare systems, focusing on its applications in clinical decision-making, disease prediction, and personalized medicine. The study analyzes current trends, benefits, and challenges associated with big data implementation. Key issues such as data integration, privacy, and ethical considerations are also discussed. The findings suggest that big data analytics enhances healthcare efficiency and patient outcomes, although significant barriers remain. The paper concludes by emphasizing the need for advanced data management strategies and interdisciplinary collaboration to fully realize the potential of big data in healthcare.